Environmental exposure to phthalates and dementia with Lewy bodies: contribution of metabolomics. Issue 9 (7th July 2020) - Agin, Arnaud; Blanc, Frédéric; Bousiges, Olivier; Villette, Claire; Philippi, Nathalie; Demuynck, Catherine; Martin-Hunyadi, Catherine; Cretin, Benjamin; Lang, Sabine; Zumsteg, Julie; Namer, Izzie Jacques; Heintz, Dimitri
Abstract : Background: In neurodegenerative diseases, alongside genetic factors, the possible intervention of environmental factors in the pathogenesis is increasingly being considered. In particular, recent evidence suggests the intervention of a pesticide-like xenobiotic in the initiation of disease with Lewy bodies (DLB). Objectives: To test for the presence of pesticides or other xenobiotics in the cerebrospinal fluid (CSF) of patients with DLB. Methods: A total of 45 patients were included in this study: 16 patients with DLB at the prodromal stage, 8 patients with DLB at the demented stage, 8 patients with Alzheimer's disease (AD) at the prodromal stage and 13 patients with AD at the demented stage. CSF was obtained by lumbar puncture and analysed by liquid chromatography–mass spectrometry. Results: Among the compounds detected in greater abundance in the CSF of patients with DLB compared with patients with AD, only one had a xenobiotic profile potentially related to the pathophysiology of DLB. After normalisation and scaling, bis(2-ethylhexyl) phthalate was more abundant in the CSF of patients with DLB (whole cohort: 2.7-fold abundant in DLB, p=0.031; patients with dementia: 3.8-fold abundant in DLB, p=0.001). Conclusions: This study is the first reported presence of a phthalate in the CSF of patients with DLB. This molecule, which is widely distributed in the environment and enters the body orally, nasally and transdermally, was first introduced in the 1920s as a plasticizer. Thereafter, the first cases of DLB were described in the 1960s and 1970s. These observations suggest that phthalates may be involved in the pathophysiology of DLB.